A Study on Acceptance of Contraceptive Device Among Female in A Rural Area of Bangladesh and Its Relation with Their Educational Level - Das, Shila Rani; Biswas, Chinmay; Raza, AKM Maruf; Chowdhury, Mehdi Ashik; Rahman, Md Sumon (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2018)
Background: Bangladesh had an official Family Planning (FP) programme beginning in 1960. Bangladesh has experienced a sevenfold increase in its Contraceptive Prevalence Rate (CPR) in less than forty years from 8% in 1975 to 62% in 2014. However, despite this progress, almost one-third of pregnancies are still unintended which may be attributed to unmet need for family planning and discontinuation and switching of methods after initiation of their use. To find out the acceptance of contraceptive devices among female in rural area of Bangladesh and its relation with their educational level. Methods : A cross sectional descriptive study of fifteen days’ duration was conducted among female in rural area of Bangladesh. Participants not willing to respond and pregnant women were excluded. Total of 120 women were selected as study participants. Every woman was interviewed face to face with pre-tested questionnaire after taking informed consent. Results: About 46.92% were age group 26 to 35 years and 11.11% were age group more than 36 years of age, 83.96% were Muslim and 14.81% were Hindu. Maximum (83.96%) were married. About 37.04% were upto class V and 1.23% were SSC passed. About 27.16% were class VI to X. About 60.49% duration of married life 1 to 10 years and 1.23% married life 30 to 40 years. 86.42% were use contraceptive device, among them 34.43% were use condom and 3.28% were used IUD. About 43.33% respondents suffer from irregular menstruation and 25% from menorrhagia, 20.84% weight gain. About 46.66% respondents had 2 children and 4.16% had no child. Conclusion: A renewed commitment from government bodies and independent organizations is needed to implement and monitor family planning strategies in order to ensure the adherence to and provision of the most appropriate contraceptive method for couples. Chatt Maa Shi Hosp Med Coll J; Vol.17 (1); Jan 2018; Page 46-49